DIGITAL IMAGE WATERMARKING (DIW) ROBUST TO GEOMETRIC TRANSFORMATIONS - Yoiceta Vanda; Setyawan Ary Cahyono (Prosiding SNST Fakultas Teknik, 2015)
Digital images can be easily copied and distributed illegally using widely available software tools. Watermarking methods that embed side information into images with the aim of protecting copyright have been proposed. So far, these methods have been defeated by simple attacks such as rotation, translation and scaling. In this research, a novel digital image watermarking system that takes advantage of the Wavelet Transform properties to embed a spread spectrum circular symmetric watermark in an image is proposed. Watermark robustness against translation, rotation and scaling attacks is achieved by the proposed method. Successful experiments showing the performance of the method to geometric. Key words: watermarking, mark, wavelet, spread spectrum circular symmetric